Optimisation of catalytic asymmetric intermolecular cyclopropanation of diazo acetoxy acetone and styrene with p-NITRO-Ru(II)-DIPHENYL-PHEOX complex - Lê, Thị Loan Chi; Iwasa, Seiji (Hue University Journal of Science: Natural Science, 2025)
The chiral cyclopropane ring is an important pharmacophore in pharmaceuticals and bioactive natural products, making libraries of these building blocks a valuable resource for drug discovery and development. Furthermore, the cyclopropyl ketone groups found in natural products have important biochemical properties, but only a-diazo acetophenone is developed as a ketone source, reported with 67% and 86% enantioselectivity yields. Therefore, this study presents a process to synthesise chiral cyclopropane of diazo acetoxy acetone and styrene catalysed by asymmetric p-nitro-Ru-¬dialkyl-pheox complex. This procedure was optimised under suitable solvent and temperature conditions and achieved high yields, excellent stereoisomer selectivity of more than 99:1, and enantioselectivity up to 95%. This is our exclusive published result, demonstrating the effectiveness of this catalyst in the reaction to produce highly stereoselective cyclopropanes. In addition, the study also has sufficient evidence on the mechanism of chiral cyclopropane formation with preferential trans product.